Pure Mathematics 1 - Neill, Hugh.; Quadling, Douglas (New York : Cambridge University press, 2007)
Pure Mathematics 1 corresponds to unit P1. It covers quadratics, functions, coordinate geometry, circular measure, trigonometry, vectors, series, differentiation and integration.
Includes index.
Keywords: Mathematics; Mathematics -- Problems, exercises, etc